A graphite material and its preparation method and use

By forming a velvet structure on the surface of graphite primary particles, the problems of low ion transmission rate and high interface compatibility in solid-state batteries are solved, and better wetting and interface performance in organic electrolytes are achieved, and the fast charging performance of solid-state batteries is improved.

CN119750566APending Publication Date: 2025-04-04HUNAN SHINZOOM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411972398.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing graphite anode materials exhibit lower ion transmission rates and higher interfacial compatibility requirements in solid-state batteries, making it difficult to meet the needs of new organic electrolytes.

Method used

By forming a prominent villi structure on the surface of the primary graphite particles, its hydrophobicity is enhanced, thereby improving wetting and interfacial compatibility in the organic electrolyte.

Benefits of technology

It achieves better wetting and interface performance of graphite materials in organic electrolytes, reduces interface transmission impedance, and improves the fast charging performance of solid-state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119750566A_ABST
    Figure CN119750566A_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of battery materials. The present invention provides a graphite material and a preparation method and use thereof. The graphite material is a graphite primary particle, and the surface of the graphite primary particle has a villi structure, and the villi structure makes the graphite material hydrophobic and lipophilic. By forming a unique villi structure on the graphite primary particle, the surface hydrophilicity is poorer but the lipophilicity is better than that of conventional graphite. The graphite primary particles can be further agglomerated to form oily secondary particles with high sphericity and concentrated particle size. This spherical composite graphite material is also more suitable for oil-based electrolytes, has better wettability and interface compatibility with them, and can effectively improve interface performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of carbon material preparation and electrode material, and relates to a graphite material and a preparation method and application thereof. Background Art

[0002] Graphite negative electrode materials, with their high stability, good conductivity and relatively low cost, occupy an important position in lithium-ion batteries, especially in today's mature electrolyte system batteries. However, with the continuous development of battery technology, solid-state batteries, as the next generation of high-performance energy storage devices, are gradually becoming a research hotspot and a new application demand. Solid-state batteries, with their advantages such as higher energy density, longer cycle life and better safety, are regarded as an effective way to solve the performance drawbacks and safety hazards of current liquid system lithium-ion batteries. However, there are significant differences between the electrolytes of solid-state batteries and liquid electrolytes, their ion transfer rates are relatively low, and the interface compatibility of electrode materials is required to be higher. How to improve graphite negative electrode materials to adapt to new organic electrolytes in order to obtain better interface compatibility and fast charging performance in the development and introduction of solid-state battery negative electrode materials is a problem that needs to be solved urgently. Summary of the invention

[0003] In view of the problems existing in the prior art, the purpose of the present invention is to provide a graphite material and a preparation method thereof and a composite graphite material and a preparation method thereof, wherein the graphite material is a graphite primary particle with a protruding villi structure on the surface, and the villi structure can enhance the hydrophobicity and lipophilicity of the graphite material. The graphite primary particles and the secondary particles formed by agglomeration thereof are more suitable for organic electrolytes, have better wettability, and can effectively improve the interface performance.

[0004] To achieve this object, the present invention adopts the following technical solutions:

[0005] In a first aspect, the present invention provides a graphite material, wherein the graphite material is a graphite primary particle, and the surface of the graphite primary particle has a protruding villi structure.

[0006] The fuzz structure enables the graphite material to have hydrophobic and oleophilic properties.

[0007] The surface of the graphite primary particles described in the present invention forms a unique villi structure, which causes the surface tension of the graphite primary particles to be larger and reduces the wettability with aqueous electrolytes. However, the surface of the villi structure itself contains aromatic hydrocarbons and ester groups and is naturally hydrophobic. The volatile matter attached to the surface of the villi structure is similar to the properties of organic electrolytes, so it has better wettability and compatibility in organic electrolytes or organic solid electrolytes, which can effectively improve the interface performance and reduce the interface transmission impedance.

[0008] The following are preferred technical solutions of the present invention, but are not intended to be limitations of the technical solutions provided by the present invention. Through the following technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0009] As a preferred technical solution of the present invention, the size of the villi structure is 10 to 2000 nm, such as 10 nm, 20 nm, 30 nm, 50 nm, 70 nm, 80 nm, 90 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm, 1200 nm, 1400 nm, 1600 nm, 1800 nm or 2000 nm, etc. The size of the villi structure is nanometer-level and smaller than the particle size of the primary particles, and can be evenly and widely distributed on the graphite surface.

[0010] As a preferred technical solution of the present invention, the particle size D of the graphite material 50 It is 4 to 25μm, for example, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm, 21μm, 22μm, 23μm, 24μm or 25μm, etc.

[0011] The second invention provides a method for preparing a graphite material, the method for preparing a graphite material comprising:

[0012] Providing coke having a volatile matter content of 3% to 18% by mass, and graphitizing the coke to obtain a graphitized material;

[0013] The graphitized material is floated in water, and the material floating on the water surface is collected to obtain primary graphite particles with a protruding villi structure on the surface.

[0014] In the preparation method of the graphite material of the present invention, high-volatile coke is used as a raw material. The volatile matter can be deposited on the surface of the particles to form a uniformly dispersed villi structure while the primary graphite particles are formed under the cooperation of graphitization treatment.

[0015] As a preferred technical solution of the present invention, the graphitization temperature is 2000-2800°C, for example, 2000°C, 2050°C, 2100°C, 2150°C, 2200°C, 2250°C, 2300°C, 2350°C, 2400°C, 2450°C, 2500°C, 2550°C, 2600°C, 2650°C, 2700°C, 2750°C or 2800°C, etc., preferably 2400-2800°C.

[0016] In the present invention, when the graphitization temperature is low, it cannot be converted into graphite crystals, the graphitization degree is extremely low, and it cannot be used as a graphite product. When the temperature is too high, the villi structure on the graphite surface will actively volatilize, and the surface volatiles are difficult to deposit, which is not conducive to the formation of the villi structure to achieve the surface hydrophobic and oleophilic effect.

[0017] As a preferred technical solution of the present invention, the mass percentage of the volatile matter of the coke is 3% to 18%, for example, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17% or 18%, etc.

[0018] In the present invention, a suitable volatile content is conducive to the deposition of the villi structure. If the volatile content is too low, too little villi structure will be effectively deposited on the surface of the primary graphite particles. If the volatile content is too high, the graphitization spray furnace will be affected, causing safety problems.

[0019] Preferably, in the focused polarization structure, the mosaic structure accounts for greater than or equal to 20% and less than or equal to 50%, for example, it can be 20%, 23%, 25%, 28%, 30%, 32%, 35%, 38%, 40%, 42%, 45%, 48% or 50%, etc.

[0020] Since it is more difficult to discharge volatiles from a mosaic structure than from a streamlined structure, in the present invention, the coke is controlled to contain an appropriate mosaic structure ratio to facilitate the deposition of volatiles during graphitization to form a villi structure.

[0021] In the present invention, the type and proportion of the image area are determined by a polarizing microscope and image analysis software; multiple images of petroleum coke are collected by a polarizing microscope, and then image analysis software such as RICC-Imager is used to automatically determine the area of ​​each image according to the light and dark extinction size, morphology, grayscale, etc. After statistical data is collected, the area proportion of wide-area streamlined structures and mosaic structures can be quantitatively analyzed.

[0022] Preferably, the coke comprises petroleum coke.

[0023] Preferably, the particle size D of the coke is 50 3 to 50μm is a conventional choice, such as 3μm, 5μm, 8μm, 10μm, 13μm, 15μm, 18μm, 20μm, 23μm, 25μm, 28μm, 30μm, 33μm, 35μm, 38μm, 40μm, 42μm, 45μm, 48μm or 50μm.

[0024] In a third aspect, the present invention provides a composite graphite material, comprising secondary particles obtained by agglomerating primary graphite particles; the surface of the primary graphite particles has a protruding villi structure.

[0025] As a preferred technical solution of the present invention, the size of the villus structure is 10 to 2000 nm, for example, 10 nm, 20 nm, 30 nm, 50 nm, 70 nm, 80 nm, 90 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm, 1200 nm, 1400 nm, 1600 nm, 1800 nm or 2000 nm, etc.

[0026] In the present invention, the particle size of the graphite primary particles matches the particle size of the coke before graphitization, and the particle size can be adjusted according to actual application requirements. Preferably, the particle size D of the graphite primary particles is 50 4 to 25 μm, for example, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22 μm, 23 μm, 24 μm or 25 μm,

[0027] In the present invention, the particle size of the composite graphite particles is increased to a certain extent compared with the particle size of the primary graphite particles before granulation. The particle size can be adjusted by conventionally adjusting the granulation degree according to actual application requirements. Preferably, the particle size D of the composite graphite material is 50 It is 5 to 50μm, for example, 5μm, 8μm, 10μm, 13μm, 15μm, 18μm, 20μm, 23μm, 25μm, 28μm, 30μm, 33μm, 35μm, 38μm, 40μm, 42μm, 45μm, 48μm or 50μm, etc.

[0028] Preferably, the material concentration of the composite graphite material is 0.95-1.05, for example, 0.95, 0.96, 0.97, 0.98, 0.99, 1, 1.01, 1.02, 1.03, 1.04 or 1.05.

[0029] In a fourth aspect, the present invention provides a method for preparing a composite graphite material, the method for preparing the composite graphite material comprising:

[0030] Providing coke having a volatile matter content of 3% to 18% by mass, and graphitizing the coke to obtain a graphitized material;

[0031] flotation the graphitized material in water, collecting the material floating on the water surface, and obtaining graphite primary particles having a protruding villi structure on the surface;

[0032] The primary graphite particles are mixed with a coating agent, granulated and coated to form secondary particles, thereby obtaining a composite graphite material.

[0033] In the preparation method of the composite graphite material of the present invention, due to the prominent villi structure on the surface of the graphite primary particles, the compatibility with the coating agent can be improved, the morphology of the secondary particles after granulation is more spherical, and the particle size concentration is better, which is conducive to improving the fast charging performance of the secondary particles. The coating agent mainly plays a coating and bonding role, and the villi structure on some primary particles will be covered, so the villi structure content on the surface of the secondary particles will be reduced, but will not disappear completely, that is, the villi structure on the surface of the graphite primary particles after granulation can still be partially retained, which can also increase the lipophilicity of the secondary particles. When the obtained composite graphite material is applied to the organic electrolyte system, it has better wettability, which can effectively improve the interface performance and reduce the interface transmission impedance.

[0034] As a preferred technical solution of the present invention, the temperature of the graphitization treatment is 2000-2800°C, for example, 2000°C, 2050°C, 2100°C, 2150°C, 2200°C, 2250°C, 2300°C, 2350°C, 2400°C, 2450°C, 2500°C, 2550°C, 2600°C, 2650°C, 2700°C, 2750°C or 2800°C, etc., preferably 2400-2800°C.

[0035] As a preferred technical solution of the present invention, the mass percentage of the volatile matter of the coke is 3% to 18%, for example, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17% or 18%, etc.

[0036] Preferably, in the focused polarization structure, the mosaic structure accounts for greater than or equal to 20% and less than or equal to 50%, for example, it can be 20%, 23%, 25%, 28%, 30%, 32%, 35%, 38%, 40%, 42%, 45%, 48% or 50%, etc.

[0037] Preferably, the coke comprises petroleum coke.

[0038] Preferably, the particle size D of the coke is 50 It is 3 to 50μm, for example, 3μm, 5μm, 8μm, 10μm, 13μm, 15μm, 18μm, 20μm, 23μm, 25μm, 28μm, 30μm, 33μm, 35μm, 38μm, 40μm, 42μm, 45μm, 48μm or 50μm, etc.

[0039] In the present invention, the type, amount and granulation and coating conditions of the coating agent are all conventionally selected and are not specifically limited.

[0040] Preferably, the coating agent comprises at least one of asphalt, tar or resin.

[0041] Preferably, the amount of the coating agent is 3% to 20% of the mass of the graphite primary particles, for example, 3%, 5%, 8%, 10%, 12%, 14%, 16%, 18% or 20%.

[0042] Preferably, the temperature of the granulation coating is 300-700°C, for example, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C or 700°C, and the time is 1-5h, for example, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h or 5h, etc.

[0043] In a fifth aspect, the present invention provides a secondary battery, wherein the secondary battery contains the graphite material described in the first aspect or the composite graphite material described in the third aspect.

[0044] Preferably, the secondary battery comprises a solid-state battery or a semi-solid-state battery.

[0045] As a preferred technical solution of the present invention, the electrolyte of the secondary battery includes an organic electrolyte.

[0046] Compared with the prior art solutions, the present invention has at least the following beneficial effects:

[0047] The present invention forms a unique villi structure on the primary graphite particles so that the surface hydrophilicity is poorer but the lipophilicity is better than that of conventional graphite. The primary graphite particles can form oily secondary particles with high sphericity and concentrated particle size. When this spherical composite graphite material is applied to an organic electrolyte system, it has better wettability and interface compatibility, can effectively improve interface performance, and reduce interface transmission impedance.

[0048] In the graphite material preparation method of the present invention, specific raw materials are used, and high volatile coke is used in conjunction with graphitization treatment, so that while primary graphite particles are formed, volatiles are deposited on the surface of the particles to form a villi structure, and the villi structure is irregular in shape and evenly distributed on the primary particles. After the primary graphite particles are granulated and coated, they agglomerate to form spherical secondary particles, and the villi structure is still partially retained, so that the obtained composite graphite material has hydrophobic and oleophilic properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 This is a SEM test image of the graphite primary particles obtained in Example 1.

[0050] Figure 2 This is a SEM test image of the graphite primary particles obtained in Example 2.

[0051] Figure 3 This is a SEM test image of the graphite primary particles obtained in Comparative Example 1.

[0052] Figure 4 This is a SEM test image of the composite graphite material obtained in Example 1.

[0053] Figure 5 This is a high-magnification SEM test image of the composite graphite material obtained in Example 1.

[0054] Figure 6 This is a high-magnification SEM test image of the composite graphite material obtained in Comparative Example 1. DETAILED DESCRIPTION

[0055] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0056] It should be clear to those skilled in the art that the embodiments are only intended to help understand the present invention and should not be considered as specific limitations of the present invention.

[0057] Example 1

[0058] This embodiment provides a graphite material, and the preparation method of the graphite material includes:

[0059] Provide a petroleum coke raw material with a volatile matter content of 12% by mass (the mosaic structure in the polarized structure accounts for 20% to 50%), and obtain a particle size D after rough crushing, shaping and classification pretreatment. 50 Petroleum coke powder of 17-18 μm;

[0060] The obtained petroleum coke powder is graphitized at a temperature of 2400° C. to obtain a graphitized material;

[0061] The graphitized material is floated in water, and the material floating on the water surface is collected to obtain primary graphite particles with a villi structure on the surface.

[0062] This embodiment also provides a composite graphite material, the preparation method of which includes:

[0063] The primary graphite particles obtained above were mixed with asphalt, with the amount of asphalt being 6% of the mass of the primary graphite particles, and granulated and coated at 500° C. for 3 hours to form secondary particles, thereby obtaining a composite graphite material.

[0064] Example 2

[0065] This embodiment provides a graphite material and a composite graphite material. In the preparation method of the graphite material, the volatile matter of petroleum coke is 3%. Except for the above, other conditions are exactly the same as those in Example 1.

[0066] Example 3

[0067] This embodiment provides a graphite material and a composite graphite material. In the preparation method of the graphite material, the volatile matter of petroleum coke is 18%. Except for the above, other conditions are exactly the same as those in Example 1.

[0068] Example 4

[0069] This embodiment provides a graphite material and a composite graphite material. In the preparation method of the graphite material, the graphitization temperature is 2000° C. Except for the above, other conditions are exactly the same as those in Example 1.

[0070] Example 5

[0071] This embodiment provides a graphite material and a composite graphite material. In the preparation method of the graphite material, the graphitization temperature is 2800° C. Except for the above, other conditions are exactly the same as those in Example 1.

[0072] Comparative Example 1

[0073] This comparative example provides a graphite material and a composite graphite material, wherein the volatile matter of petroleum coke in the preparation method of the graphite material is 1%. In this comparative example, since the primary graphite particles have no villi structure, almost all of the particles settle after flotation, the primary graphite particles that have not been flotated are used to granulate and prepare secondary particles.

[0074] Except for the above, other conditions are exactly the same as those in Example 1.

[0075] Comparative Example 2

[0076] This comparative example provides a graphite material and a composite graphite material. In the preparation method of the graphite material, the volatile matter of petroleum coke is 21%. Except for the above, other conditions are exactly the same as those in Example 1. In this comparative example, because the volatile matter of petroleum coke is too high, the furnace is sprayed during the graphitization process, and the graphite material and the composite graphite material cannot be obtained.

[0077] Comparative Example 3

[0078] This comparative example provides a graphite material and a composite graphite material, wherein the graphitization temperature in the preparation method of the graphite material is 3000° C. In this comparative example, since the primary graphite particles have no villi structure, almost all the particles settle after flotation, so the primary graphite particles that have not been flotated are used to granulate and prepare secondary particles.

[0079] Except for the above, other conditions are exactly the same as those in Example 1.

[0080] Comparative Example 4

[0081] This comparative example provides a graphite material and a composite graphite material, wherein the preparation method of the graphite material replaces petroleum coke with anisotropic needle coke (in the polarized structure, the proportion of the mosaic structure is less than 20%). In this comparative example, since the primary graphite particles have no villi structure, almost all of the particles settle after flotation, the primary graphite particles that have not been flotated are used to granulate and prepare secondary particles.

[0082] Except for the above, other conditions are exactly the same as those in Example 1.

[0083] Characterization and Testing:

[0084] Ⅰ. The graphite materials (graphite primary particles) and composite graphite materials (secondary particles) obtained in each example and comparative example were characterized by SEM. Figure 1 , Figure 2 and Figure 3 The following are SEM test images of graphite primary particles obtained in Example 1, Example 2 and Comparative Example 1, respectively. Figure 1 As shown, it can be seen that the surface of the graphite primary particles obtained in Example 1 is covered with fine villi structures, while the surface of the graphite primary particles in Comparative Example 1 is smooth, with only dispersed large particles existing, and no villi structures are formed. Figure 4 and Figure 5 is a SEM image of the composite graphite material obtained in Example 1, Figure 6 This is an SEM image of the composite graphite material obtained in Example 1. As shown in the figure, it can be seen that the primary graphite particles in Example 1 can be agglomerated into secondary particles with high sphericity, concentrated particle size and excellent dispersion, while the agglomerated particles obtained in Example 1 have irregular morphology and poor sphericity.

[0085] The size range of the villi structure of the graphite materials obtained in the examples and comparative examples was estimated in a SEM test, and the results are shown in Table 1.

[0086] II. The graphite materials (graphite primary particles) and composite graphite materials (secondary particles) obtained in each embodiment and comparative example were tested for particle size: using Malvern 3000 testing equipment, ultrasonically dispersing the sample materials with alcohol as a dispersant, and then testing. The results are shown in Table 1.

[0087] Table 1

[0088]

[0089] Note: The spherical or irregular morphology of the secondary particles in Table 1 is the result of visual observation of the particle morphology through SEM.

[0090] III. Performance test:

[0091] The graphite materials (primary particles) and composite graphite materials (secondary particles) obtained in each embodiment and comparative example are added to CMC, SP and SBR as negative electrode materials for proportioning to obtain negative electrode slurry, which is evenly coated on the surface of copper foil to make negative electrode plates; matched with positive electrode plates (using aluminum foil) of ultra-high nickel positive electrode ternary materials, polymer solid electrolyte polyethylene oxide (PEO) modified material electrolyte is used, and after winding, packaging and formation, a battery cell is obtained for testing. Among them, the DCR test is the resistance generated inside the battery when a direct current passes through it. By applying a constant current to the battery and measuring the voltage change at both ends at the same time, the DCR value is calculated. Specifically, a blue cabinet is used for testing at 25 / -20℃±5℃; relative humidity 15%~90%; atmospheric pressure 86kPa~106kPa. The fast charging level is determined by charging and discharging the battery cells at a specified current (rate) and then disassembling the battery. If there is no lithium deposition on the battery interface, the battery passes the fast charging test at this rate. The fast charging level is confirmed at the highest rate that can pass the test.

[0092] The results are shown in Table 2.

[0093] Table 2

[0094]

[0095] Note: Since there is basically no particles after flotation in the comparative example without villi structure, conventional graphite particles without flotation were selected for subsequent testing.

[0096] It can be seen from Table 1 and Table 2 that:

[0097] (1) In Examples 1-3, when the material particle size specifications are similar, the different volatile components of the raw materials cause different amounts of villi deposited on the surface of the single particles, resulting in differences in the relevant interface transmission impedance. The components with higher volatile components in Examples 1 and 3 have larger amounts of villi structure deposited, lower impedance, and better corresponding fast charging performance;

[0098] (2) When the material specifications of Example 1 and Example 4-5 are the same, by controlling the graphitization temperature, it is found that the higher the graphitization temperature, the less the villi structure, and the optimal temperature for villi formation is between 2400-2800 degrees. Similarly, the composite particles of Example 1 and 5 have better fast charging effects.

[0099] (3) Example 1 and Comparative Examples 1 and 2 show that the volatile matter is too low. A volatile matter below 3% causes the surface of the graphite primary particles to fail to deposit and form a fluff structure. A volatile matter that is too high will cause the graphitization furnace to fail to effectively form a fluff structure. Example 1 containing a fluff structure has significantly improved fast charging performance compared to Comparative Example 1.

[0100] (4) Example 1 and Comparative Example 3 show that too high a graphitization temperature will cause the volatile matter to overflow quickly, and it will be impossible to deposit and produce a villi structure. Example 1 containing a villi structure has excellent fast charging capability.

[0101] (5) Examples 1-5 and Comparative Example 4 illustrate that, under the conditions of consistent volatile matter and graphitization, if a streamlined anisotropic coke raw material is used, the volatile matter cannot be effectively retained, resulting in difficulty in generating a villi structure. The lack of a villi structure leads to poor fast charging performance.

[0102] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0103] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0104] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A graphite material, characterized in that: The graphite material is graphite primary particles, and the surface of the graphite primary particles has a protruding villi structure.

2. The graphite material according to claim 1, characterized in that The size of the villi structure is 10 to 2000 nm; Preferably, the particle size D of the graphite material is 50 4~25μm.

3. A method for preparing the graphite material according to claim 1 or 2, characterized in that: The preparation method of the graphite material comprises: Providing coke having a volatile matter content of 3% to 18% by mass, and graphitizing the coke to obtain a graphitized material; The graphitized material is floated in water, and the material floating on the water surface is collected to obtain primary graphite particles with a protruding villi structure on the surface.

4. The method for preparing the graphite material according to claim 3, characterized in that: The graphitization temperature is 2000-2800°C, preferably 2400-2800°C.

5. The method for preparing the graphite material according to claim 3 or 4, characterized in that: In the polarized structure of the focus, the mosaic structure accounts for greater than or equal to 20% and less than or equal to 50%; Preferably, the coke comprises petroleum coke; Preferably, the particle size D of the coke is 50 3~50μm.

6. A composite graphite material, characterized in that: The composite graphite material comprises secondary particles obtained by agglomerating primary graphite particles; the surfaces of the primary graphite particles have a protruding villi structure.

7. The composite graphite material according to claim 6, characterized in that: The size of the villi structure is 10 to 2000 nm; Preferably, the particle size D of the graphite primary particles is 50 4~25μm; Preferably, the particle size D of the composite graphite material is 50 5~50μm; Preferably, the material concentration of the composite graphite material is 0.95-1.

05.

8. A method for preparing the composite graphite material according to claim 6 or 7, characterized in that: The preparation method of the composite graphite material comprises: Providing coke having a volatile matter content of 3% to 18% by mass, and graphitizing the coke to obtain a graphitized material; flotation the graphitized material in water, collecting the material floating on the water surface, and obtaining graphite primary particles having a protruding villi structure on the surface; The primary graphite particles are mixed with a coating agent, granulated and coated to form secondary particles, thereby obtaining a composite graphite material.

9. The method for preparing a composite graphite material according to claim 8, characterized in that: The temperature of the graphitization treatment is 2000-2800°C, more preferably 2400-2800°C; Preferably, in the polarized structure of the focus, the proportion of the mosaic structure is greater than or equal to 20% and less than or equal to 50%; Preferably, the coke comprises petroleum coke; Preferably, the particle size D of the coke is 50 3~50μm; Preferably, the coating agent comprises at least one of asphalt, tar or resin; Preferably, the amount of the coating agent is 3% to 20% of the mass of the graphite primary particles; Preferably, the granulation coating is carried out at a temperature of 300 to 700° C. and for a time of 1 to 5 hours.

10. A secondary battery, characterized in that: The secondary battery contains the graphite material according to claim 1 or 2 or the composite graphite material according to claim 6 or 7; Preferably, the secondary battery comprises a solid-state battery or a semi-solid-state battery.